2019
DOI: 10.3233/prm-180596
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and goal attainment with spinal orthoses for children with cerebral palsy

Abstract: PURPOSE: Analyze the goals for treatment and attained goals for spinal orthoses in children with cerebral palsy (CP), and describe the use of spinal orthoses in relation to age, sex, gross motor function, and scoliosis. METHODS: Cross-sectional data for all children born between 2000 and 2014 and registered in the Swedish CP registry were analyzed in relation to age, sex, Gross Motor Function Classification System (GMFCS), and scoliosis. Treatment goals were to 1) preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
(41 reference statements)
1
20
0
Order By: Relevance
“…The Gross Motor Function Classification System (GMFCS) levels III, IV, and V have been identified as risk factors for scoliosis in children with CP (Loeters et al 2010, Hägglund et al 2018a. New findings suggest that girls with CP have a higher risk than boys of developing scoliosis (Bertoncelli et al 2017, Hägglund et al 2018a, Pettersson et al 2019, and that epilepsy is another independent risk factor (Bertoncelli et al 2017). Lateral displacement of the hips, hip dislocations, and previous hip surgery are sometimes associated with neuromuscular scoliosis (Persson-Bunke et al 2006, Bertoncelli et al 2017, Hägglund et al 2018b, whereas successful hip surveillance leading to a reduced number of dislocated hips results in a lower proportion of scoliosis (Hägglund et al 2014).…”
mentioning
confidence: 99%
“…The Gross Motor Function Classification System (GMFCS) levels III, IV, and V have been identified as risk factors for scoliosis in children with CP (Loeters et al 2010, Hägglund et al 2018a. New findings suggest that girls with CP have a higher risk than boys of developing scoliosis (Bertoncelli et al 2017, Hägglund et al 2018a, Pettersson et al 2019, and that epilepsy is another independent risk factor (Bertoncelli et al 2017). Lateral displacement of the hips, hip dislocations, and previous hip surgery are sometimes associated with neuromuscular scoliosis (Persson-Bunke et al 2006, Bertoncelli et al 2017, Hägglund et al 2018b, whereas successful hip surveillance leading to a reduced number of dislocated hips results in a lower proportion of scoliosis (Hägglund et al 2014).…”
mentioning
confidence: 99%
“…This is echoed in earlier work by Sahinoglu et al [33] who found that both adjustable seating and custom molded seating was required for the children with more postural asymmetries, and Neilson et al [34] who reported on improved quality of life and sitting posture through the provision of customized seating for adults with profound postural disabilities. Furthermore, the use of spinal orthoses may improve head control, stability, and arm-hand function of children with CP [35] and ultimately promote participation in activity and reduce pain [36]. The prevalence of pain was reported by 39% of the children and/or their caregivers in this study, similar to Alriksson-Smidt and H€ agglund [9], who found that approximately one third of Swedish children with CP aged 1-14 years had pain, and that the occurrence of pain increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…Although for children with neuromuscular conditions, TLSOs are more commonly recommended to slow progression of spinal curves until such time as spinal instrumentation surgery is viable [1], they have also been suggested as a means of improving sitting balance and arm function [35]. In a study of 251 children with cerebral palsy who used TLSO's, most (96%) used them with the goal of improving stability and positioning while 51% used them to promote head control and 38% to improve hand control [61]. In Tom's case, the TLSO allowed him to use mobility equipment other than his power wheelchair and it enhanced function in his manual wheelchair, tricycle and dynamic mobility device.…”
Section: Functionmentioning
confidence: 99%